The Differences between the Management Models Advocated in Tao Tek King and the Bible - Han Ruihui (Archives of Current Research International, 2016)
Tao Tek King and the Bible represent the Oriental and Christian management thought system. Tao Tek King emphasizes action through inaction, while the Bible, especially the Old Testament, has many laws given by God, which embodies many restrictions as the management measures. In the sense, the thoughts in the Bible and Tao Tek King are in contrast. In the Bible, human being is sinful and tend to committing crimes. So the management model it advocates in Old Testament depends on the restrictions, which belongs to Otherness. However, Tao Tek King believes that the leaders should not interfere with the routines and lives of people, because Tao Tek King proposes that the goodness lies in the society and nature, which means goodness does not exist in Otherness. The two different kinds of management both achieve success, but they both have the defects. In the management tradition influenced by the Bible, the management depends too much on the Otherness, so it causes the unnatural and unstable condition, which is one part of the modern social problems. There are no perfect leaders morally in the world, so what the Tao Tek King describes about the management is only ideal, therefore it is too hard to be realized in practice.